A Systematic Literature Review on the Role of Artificial Intelligence in Digital Marketing Strategies - Shofiana Syam (Pustaka Digital Indonesia, 2025)
Artificial Intelligence (AI) has revolutionized digital marketing by enhancing personalization, automating customer interactions, and optimizing marketing strategies. AI-powered tools, including chatbots, predictive analytics, recommendation systems, and automated content generation, have transformed how businesses engage with consumers. This study conducts a systematic literature review (SLR) to examine AI’s role in digital marketing, focusing on its applications, benefits, and challenges. Using data from Scopus, Web of Science, and Google Scholar, this review analyzes key AI-driven marketing strategies and their impact on customer engagement, conversion rates, and overall marketing efficiency. The findings indicate that AI enhances marketing effectiveness by enabling real-time personalization, improving customer targeting, and streamlining content creation. Businesses leverage AI to analyze vast amounts of consumer data, allowing for accurate predictions of consumer behavior and preferences. However, AI implementation in digital marketing presents challenges, including data privacy concerns, ethical issues, algorithmic bias, and high implementation costs. Moreover, consumer trust in AI-driven marketing varies, influencing acceptance and engagement levels. This study provides valuable insights for academics and practitioners on how AI is reshaping digital marketing landscapes. It highlights the need for balancing AI-driven automation with ethical considerations and consumer expectations. Future research should explore strategies for ethical AI adoption, enhancing consumer trust, and optimizing AI-driven decision-making. Addressing these challenges will enable businesses to fully harness AI’s potential for more effective and transparent marketing strategies.